Optimal Two Parameter Bounds for the Seiffert Mean - Hui Sun; Ying-Qing Song; Yu-Ming Chu (Journal of Applied Mathematics)
We obtain sharp bounds for the Seiffert mean in terms of a two parameter family of means. Our results generalize and extend the recent bounds presented in the Journal of Inequalities and Applications (2012) and Abstract and Applied Analysis (2012).